Recovery of normal esophageal function in a kitten with diffuse megaesophagus and an occult lower esophageal stricture. Issue 6 (June 2015) - Schneider, Jaycie; Ames, Marisa; DiCicco, Michael; Savage, Mason; Atkins, Clarke; Wood, Michael; Gookin, Jody L
An 8-week-old male domestic shorthair was presented to the Internal Medicine Service at North Carolina State University for regurgitation. Radiographic diagnosis of generalized esophageal dilation and failure of esophageal peristalsis were compatible with diagnosis of congenital megaesophagus. Endoscopic examination of the esophagus revealed a fibrous stricture just orad to the lower esophageal sphincter. Conservative management to increase the body condition and size of the kitten consisted of feeding through a gastrostomy tube, during which time the esophagus regained normal peristaltic function, the stricture orifice widened in size and successful balloon dilatation of the stricture was performed. Esophageal endoscopy should be considered to rule out a stricture near the lower esophageal sphincter in kittens with radiographic findings suggestive of congenital megaesophagus. Management of such kittens by means of gastrostomy tube feeding may be associated with a return of normal esophageal motility and widening of the esophageal stricture, and facilitate subsequent success of interventional dilation of the esophageal stricture.